Penetapan Kelas Kemampuan Lahan Dan Arahan Rehabilitasi Lahan Das Wai Batu Merah Kota Ambon Provinsi Maluku - Rafael M Osok; Silwanus M Talakua; Dhanang Supriadi (Faculty of Agriculture, Pattimura University, 2018)
Land use planning requires a proper consideration, so that the function of land can take place continuously and sustainably. The objectives of the research were to establish the land capability class of Wai Batu Merah watershed its land use management in accordance with each land capability class. The research method was survey with synthetic and analytical approaches, and flexible observation distance following physiographic change, soil type and land use within landunits. The results of the study showed that Wai Batu Merah watershed has 6 class and 12 sub-class land capability of II.B,KE3,e1, III.e2, III.C, IV.b2, IV.D,b2, IV.D, VI.e4, VI.E, VII.e5, VII.F,e5, VII.F, and VIII.t5 with limiting factors of slope steepness, erosion sensitivity, percentage of gravel and rock, and soil texture. Land use management planning in the Wai Batu Merah watershed includes intensive, medium, and limited agriculture, intermediate and limited grazing, agroforestry, protection forest, forest, home garden, biopores and organic materials.Keywords: Land Capability Class, Wai Batu Merah Watershed